Effect of Pro12Ala polymorphism of PPARG gene on lipid peroxidation and antioxidant defense in patients with type 2 diabetes depending on the duration of the disease - V. Y. Mokrii; S. V. Ziablytsev (Patologìâ)
Aim – to study the impact of polymorphic marker rs1801282 of gene PPARG on the formation of oxidative stress in terms of LPO and AOS in patients with type 2 diabetes depending on the duration of the disease.